2019
DOI: 10.3390/ani9110906
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Decreasing Dietary Crude Protein on the Growth Performance, Feed Efficiency and Meat Quality of Finishing Charolais Bulls

Abstract: Simple SummaryLivestock production emerges as one of the main contributors of ammonia emissions; in fact, as the literature reports, the excess of nitrogen fed in form of feed protein is excreted in manure and converted into ammonia. Defining beef cattle protein requirements, specifically for each breed and farming system, is fundamental to ensuring an adequate supply of protein, while avoiding N losses due to an over-estimation of needs. In this study, we compared two different levels of protein in beef cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…In the present study, the 12.0% CP diet seemed to limit the growth performance of Anhui white goats. That decreasing protein content of the diet's compromising daily weight gain was also observed in finishing Charolais bulls [24]. It is of great importance to formulate diets that foster the digestibility and utilization of feed stuff [25].…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, the 12.0% CP diet seemed to limit the growth performance of Anhui white goats. That decreasing protein content of the diet's compromising daily weight gain was also observed in finishing Charolais bulls [24]. It is of great importance to formulate diets that foster the digestibility and utilization of feed stuff [25].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, the meat color can also be evaluated by calculations using a * and b * value in the form of chroma ( C * = [ a * 2 + b * 2 ] 1/2 ) and hue ( H * = tan −1 [ b */ a *]). There are numerous articles that have been published reporting the effects of protein levels on meat color, and the low CP level increased the meat color value especially L * compared with HP levels (Cortese et al, 2019; Prado et al, 2015). In this experiment, the L *, a *, b *, C *, and hue angle of LD from the LP lambs scored higher than the HP lambs ( P < 0.05; Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…As the LP diet contained lower levels of nutrients than other two diets, the sheep in the LP group exhibited poorer growth performance, as shown by the lower hot carcass weight, net meat (including the fat) weight, and bone weight. Furthermore, Cortese et al [31] reported that the carcass yield of Charolais bulls was not affected by increased dietary protein levels. Luo et al [28] also showed that there were no differences in backfat thickness and carcass yield in fattening pigs fed with different levels of β-glucan supplementation.…”
Section: Carcass Traitsmentioning
confidence: 99%